Performance evaluation and emission characteristics of biodiesel-ignition enhancer blends propelled in a research diesel engine. Issue 4 (16th March 2019) - Joy, Nivin; Yuvarajan, Devarajan; Beemkumar, Nagappan
ABSTRACT: This study details the effect of the Di-Methyl-Ether(DME) as a cetane improver on neat cashew nut shell biodiesel (CBD100) to assess the emission and performance engine characteristics. Four fuels, namely, diesel, biodiesel (Cashew nut shell Methyl Ester), a blend of CBD100-10% and 20% by volume of DME (CBD90DME10and CBD80DME20) are prepared and tested on a stationary research diesel engine. The experimental parameters for CBD80DME20 showed a 1.6% increase in thermal efficiency thereby reducing 4.1% of fuel consumption than the neat biodiesel at peak conditions. Experimental result exposed that 20% of DME reduces 3.4% CO, 4.2% HC and 8.8% NOx and 8.4% smoke emissions of CBD100. Based on the outcome of this work, it is clear that CBD80DME20 shall be employed as a substitute fuel for diesel engine. Abbreviations : CI: Compression ignition; CBD100: Cashew nut shell Bio-diesel; DME: Di-methyl ether; CO: Carbon monoxide; BTE: Brake thermal efficiency; BSFC: Brake specific fuel consumption; CBD100: 100% Biodiesel; CBD90DME10: 90% biodiesel + 10% di-methyl-ether; CBD80DME20: 80% biodiesel + 20% di-methyl-ether; HC: Hydrocarbon; NOx : Oxides of nitrogen.